If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(3x + 1) = 10(x + 2) + -2x + 1 Reorder the terms: -5(1 + 3x) = 10(x + 2) + -2x + 1 (1 * -5 + 3x * -5) = 10(x + 2) + -2x + 1 (-5 + -15x) = 10(x + 2) + -2x + 1 Reorder the terms: -5 + -15x = 10(2 + x) + -2x + 1 -5 + -15x = (2 * 10 + x * 10) + -2x + 1 -5 + -15x = (20 + 10x) + -2x + 1 Reorder the terms: -5 + -15x = 20 + 1 + 10x + -2x Combine like terms: 20 + 1 = 21 -5 + -15x = 21 + 10x + -2x Combine like terms: 10x + -2x = 8x -5 + -15x = 21 + 8x Solving -5 + -15x = 21 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -5 + -15x + -8x = 21 + 8x + -8x Combine like terms: -15x + -8x = -23x -5 + -23x = 21 + 8x + -8x Combine like terms: 8x + -8x = 0 -5 + -23x = 21 + 0 -5 + -23x = 21 Add '5' to each side of the equation. -5 + 5 + -23x = 21 + 5 Combine like terms: -5 + 5 = 0 0 + -23x = 21 + 5 -23x = 21 + 5 Combine like terms: 21 + 5 = 26 -23x = 26 Divide each side by '-23'. x = -1.130434783 Simplifying x = -1.130434783
| 8-4m+5-6m= | | 37=X+3X-4 | | 15c-8c=20c-13 | | Y=4-3(1.33) | | 4n/5-1/5=2n/5 | | 2.95*1=4x | | 11.97=x/1.2 | | 2.95*4=1x | | 3(2x+1)=7x | | (2x-pi/4)=-1 | | 3y+8=2y-2 | | 20=4y+8x | | 6g+2g+g=81 | | 12x+4y-6=0 | | -16t^2+24t+30=0 | | ln(60y+100)-ln(100)=-(ln(180x-30)-ln(30)) | | 3(2+x)=8(x-2) | | 8+7g=15 | | -13u-16=2-14u | | 4r+8p-2r+5p= | | 16n=-17+15n | | 5*5=30 | | -2x+-6=-6x+-2 | | -20k-16=14-8k-17k | | 5s=6s-10 | | 3r-9=10-8r+3 | | f(x)=x+18 | | 5x-14+2x+7=180 | | ln(t)=ln(x)+1 | | ln(t)=ln(x)+3.37 | | 10+w=-w-10 | | (1+1+.92+.83)*X=18.75 |